Two Case of Patient with the Pain of Popliteal Part Treated by Scolopendrid Pharmacopuncture - Seok-woo Choi; Jin-seung Bae; Young-joo Kim (Korean Pharmacopuncture Institute, 2007)
Objectives : This study is to report the effect of Scolopendrid Pharmacopuncture on two patients suffering from the pain of popliteal part. Methods : We treated the patients with the pain of popliteal part by acupuncture according to meridian(Taeyang and Soyang-Meridian), and we injected 0.10.2cc of Scolopendrid Pharmacopuncture to his pain site. And then we evaluated their pain by VAS(Visual Analog Scale). Results : 1. A combined treatment-Scolopendrid Pharmacopuncture and Acupucture- had a very excellent effect on relieving pain of popliteal part originated from trigger point and referred pain of Popliteus or Biceps Femoris. 2. It appears that Scolopendrid Pharmacopuncture is very effective against trigger point of muscle and pain site fixed.